Experimental implementation of a catalytic membrane reactor for the direct synthesis of DME from H2+CO/CO2. (28th April 2021) - Rodriguez-Vega, Pablo; Ateka, Ainara; Kumakiri, Izumi; Vicente, Hector; Ereña, Javier; Aguayo, Andres T.; Bilbao, Javier
Graphical abstract: Highlights: A hydrophilic LTA membrane was implemented in a fixed-bed reactor for DME synthesis. H2 O separation gives to The Packed Bed Membrane Reactor advantages over the PBR. The partial separation of H2 O from the reaction medium boosts XCO 2 and YDME . DME synthesis can be performed at higher temperature on Packed-Bed-Membrane-Reactor. Abstract: The direct synthesis of dimethyl ether (DME) by the hydrogenation of CO2 and CO2 /COx mixtures has been studied in an original packed bed membrane reactor (PBMR). The role of the hydrophilic LTA zeolite membrane is to remove H2 O from the reaction medium, reducing therefore the thermodynamic limitations of methanol synthesis and dehydration stages. LTA zeolite has the best permeation properties among the studied zeolites (LTX and SOD). The experiments were carried out using a CuO-ZnO-ZrO2 /SAPO-11 catalyst at 275–325 °C, 10–40 bar, space time of 10 gcat h (molC ) −1 and using in the permeate section a sweeping gas flowrate of the same composition as that fed to the reaction section. The results (DME yield, CO2 conversion and product distribution) of the PBMR are compared with those obtained in PBR without membrane. In the hydrogenation of CO2, a DME yield of 12% and a CO2 conversion of 20% are obtained at 275 °C, 40 bar and space time of 10 gcat h (molC ) −1 with a great catalyst stability.